Long-Term Efficacy of Low-Intensity Single Donor Fecal Microbiota Transplantation in Ulcerative Colitis and Outcome-Specific Gut Bacteria - Ren, Rongrong; Gao, Xuefeng; Shi, Yichao; Li, Jianfeng; Peng, Lihua; Sun, Gang; Wang, Zikai; Yan, Bin; Zhi, Junli; Yang, Yunsheng (Frontiers in Microbiology, 2021)
Aims: To assess the long-term efficacy and safety of single-donor, low-intensity fecal microbiota transplantation (FMT) in treating ulcerative colitis (UC), and to identify the outcome-specific gut bacteria. Design: Thirty-one patients with active UC (Mayo scores≥3) were recruited, and all received FMT twice, at the start of the study and 2~3 months later respectively, with a single donor and a long-term follow-up. The fecal microbiome profile was accessed via 16s rRNA sequencing before and after FMT. Results: After the first FMT, 22.58% (7/31) of patents achieved clinical remission and endoscopy remission, with the clinical response rate of 67.74% (21/31), which increased to 55% (11/20) and 80% (16/20) respectively after the second FMT. No serious adverse events occurred in all patients. During four years of follow-up, the mean remission period of patients was 26.5±19.98m; the relapse rate in the 12 remission patients was 33.33% within one year, and 58.3% within four years. At baseline, UC patients showed an enrichment in some proinflammatory microorganisms compared to the donor, such as Bacteroides fragilis, Clostridium difficile, and Ruminococcus gnavus, and showed reduced amounts of short-chain fatty acid (SCFA) producing bacteria especially Faecalibacterium prausnitzii. FMT induced taxonomic compositional changes in the recipient gut microbiota, resulting in a donor-like state. Given this specific donor, UC recipients with different outcomes showed distinct gut microbial features before and after FMT. In prior to FMT, relapse was characterized by higher abundances of Bacteroides fragilis and Lachnospiraceae incertae sedis, together with lower abundances of Bacteroides massiliensis, Roseburia, and Ruminococcus; Preveotella copri was more abundant in the non-response patients; and the patients with sustained remission had a higher abundance of Bifidobacterium breve. After FMT, NR patients had a lower level of Bifidobacterium compared to other response group, while a higher level of multiple Bacteroides spp. was observed in the relapse patients. Conclusion: Low-intensity FMT with a single donor could induce remission in active UC, with a high level of long-term efficacy and safety. The gut microbiota composition in a UC recipient at baseline may be predictive for their response to FMT from a specific donor.